Perbedaan Status Gizi Dan Ketahanan Fisik Berdasarkan Tingkat Kerutinan Bermain Pump Pada Remaja Di Komunitas “A” Kota Semarang - Widiarista, Ayu Diah; Widajanti, Laksmi; Fatimah P., Siti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Nutritional status is positively correlated to human physical quality. A good nutritional status will affect one’s physical endurance. The goal of this research is to find out the difference of nutritional status and physical endurance based on regularity of playing pump toward teenagers in community “A” in Semarang city.This research can be classified as analytical research, using cross-sectional design. Data are collected using interview and anthropometric measurements. There 34 respondents as sample of this research. Sampling method used in this research is simple random sampling system. Data would be analyzed using independent t-test sampling.The result suggested that most of the respondents do not perform physical activities (playing pump) regularly (58,8%). Respondents with regular physical activity, all of which is as much as 100% in the category of normal nutritional status . Respondents with no regular physical activity was obtained by 95% had normal nutritional status. Respondents with regular physical activity gained 92.9% had physical endurance in the medium category, 7,1% of respondents in the category of less. Respondents who had no regular physical activity , 80 % of respondents have physical endurance medium category and 20% in the category of less physical endurance .There is a difference between those who perform phyiscal activities regularly compared to those who do not perform it regularly (p-value 0,043 < 0,05). There is also a difference in physical endurance between those who perform regular physical activities to those who do not perform it regularly(p-value 0,016 < 0,05). There are differences in nutritional status and physical endurance by level of regularity play pump in the community